1956
DOI: 10.1152/ajplegacy.1956.184.2.287
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cycle Length Upon Refractory Period of Auricles, Ventricles, and A-V Node in the Dog

Abstract: The functional refractory periods (FRP) of auricular and ventricular muscle, and of the A-V transmission system were estimated in the denervated dog heart. In all three tissues the FRP was found to be a curvilinear function of the immediately preceding cycle length, with values for all but very early premature beats falling close to the curve describing the basic cycles; that is, there was no evidence for a cumulative effect of frequency. In the auricle, the FRP of even the earliest possible premature beats ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
1
2

Year Published

1965
1965
1999
1999

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(46 citation statements)
references
References 0 publications
4
39
1
2
Order By: Relevance
“…As heart rate is inversely related to age (16,21), and as refractory periods are related to heart rate (5,20), faster heart rates in children could account for the shorter refractory periods. Friedman et al (10) demonstrated shorter refractory periods in isolated lamb ventricular myocardium compared with adult sheep, suggesting that age may be an additional factor.…”
Section: Discussionmentioning
confidence: 99%
“…As heart rate is inversely related to age (16,21), and as refractory periods are related to heart rate (5,20), faster heart rates in children could account for the shorter refractory periods. Friedman et al (10) demonstrated shorter refractory periods in isolated lamb ventricular myocardium compared with adult sheep, suggesting that age may be an additional factor.…”
Section: Discussionmentioning
confidence: 99%
“…Rosenblueth, Mendez, and their respective collaborators indicate that the functional refractory period of excitable tissue is the shortest attainable interval between two induced responses when the second stimulus is delivered at 2 or more times the threshold intensity (1,3,9). They emphasized, however, that this value is attended by an error equal to any difference that might occur in the propagation time from the point of stimulation to the point of recording between the first and second responses.…”
Section: Discussionmentioning
confidence: 99%
“…This period, during which a propagated action potential cannot be evoked by a stimulus, has been designated the "effective refractory period" (2), and the effective refractory period thus limits the maximal rate at which depolarizations can occur. When normal atrioventricular (AV) conduction takes place, the ventricular contraction rate is limited by the AV nodal system, which has been shown in experimental animals to have a longer effective refractory period than atrial or ventricular tissue (3). In spite of the fundamental importance of the refractory period of the AV nodal conduction system, this interval has heretofore been estimated only from electrocardiograms obtained from patients with spontaneous cardiac arrhythmias (4).…”
mentioning
confidence: 99%
“…The functional refractory period of the AV node is the minimum response interval between conducted basic, H,, and conducted premature, H 2 , bundle of His responses propagated from the atrium (13). The functional refractory period of the AV conduction system is the minimum response interval between conducted basic, V,, and conducted premature, V 2 , ventricular responses propagated from the atrium (14 …”
Section: Definitionsmentioning
confidence: 99%